FeS2 Nanocrystal Ink as a Catalytic Electrode for Dye-Sensitized Solar Cells - Wang, Ying-Chiao; Wang, Di-Yan; Jiang, You-Ting; Chen, Hsin-An; Chen, Chia-Chun; Ho, Kuo-Chuan; Chou, Hung-Lung; Chen, Chun-Wei (Angewandte Chemie International Edition, 2013)
Calligraphic counter electrodes: An important photovoltaic application using FeS2 nanocrystal (NC) pyrite ink to fabricate a counter electrode as an alternative to Pt in dye‐sensitized solar cells is demonstrated. FeS2 NC ink exhibits excellent electrochemical catalytic activity and remarkable electrochemical stability. ITO=indium‐doped tin oxide.